Survei Demografi Kejadian BBLR di RSUD Pangeran Jaya Sumitra - Astuti Rizki Perdana; Sismeri Dona; Putri Vidiasari (Pusat Riset dan Inovasi Nasional, 2023)
Babies with Low Birth Weight is a health problem that contributes to infant mortality. Low birth weight babies are not only at risk of death in the early months of life, but also at risk for other health problems. The purpose of the study was to determine the demographic survey of BBLR events. This research method was carried out with quantitative descriptiveness. The sample amounted to 28 BBLR events at Pangeran Jaya Sumitra Hospital from June to November 2022 analyzed univariately. The results of the univariate analysis are the highest maternal age in the range of 20-35 years (92.9%), the most maternal education at the secondary level (78.6%), the variable location of residence which almost entirely comes from Kotabaru Regency which is 96.4%, based on the area where the most lives are obtained from urban areas which is 57.1%, and the most parity variable at number 1 which is 39.3%. The implication of the study is that the results of demographic surveys about the incidence of low birth weight in hospitals can be used to screen the potential occurrence of low birth weight in mothers who are preparing for pregnancy or are pregnant.